A realistic and real-time watercolour painting engine using domain decomposition scheme. (2015) - Oh, Junkyu; Seo, Yong-Ho; Kwon, Taesoo; Park, Jinho
We present an efficient watercolour painting system, which can work interactively on low-powered computing machines, even mobile devices. A subdomain based lattice Boltzmann method (LBM) is applied to guarantee realism of the simulated watercolour painting output and to enhance the computational efficiency. Our system reflects essential features of watercolour painting such as diffusion, pigment mixing, and drying. We provide an improved colour model, which is adequate for handling subtractive pigment mixing. Results from experiments show that our system can perform interactively, and can even be utilised even for professional art work.